Fragrant olive (Osmanthus fragrans Lour.) flower extract attenuates dexamethasone-induced muscle atrophy through stimulation of PI3K/Akt pathway in C2C12 myotubes and C57BL/6 mice - Taeuk Kim; Seungok Lee; Sein Lee; Hyejung Han; Chul-Hong Kim; Dong-Woo Lee; Jae-Kwan Hwang (Journal of Functional Foods)
Maintaining protein homeostasis is crucial to prevent muscle wasting caused by an imbalance between muscle protein synthesis and degradation. In this study, in vitro and in vivo experiments were performed using C2C12 myotubes and C57BL/6 mice treated with dexamethasone to investigate the anti-atrophic effects of Osmanthus fragrans water extract (OFWE). In C2C12 myotubes, OFWE improved the protein synthesis by upregulating the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin pathway and muscle differentiation by activating myogenesis-related genes. Moreover, OFWE treatment reduced muscle protein degradation by regulating the nuclear translocation of forkhead box O3a and the expression of E3 ubiquitin ligases. In an animal model, OFWE administration was shown to increase muscle mass, myofiber size, and exercise capacity. OFWE also activated the PI3K/Akt pathway and inhibited protein catabolism. In conclusion, OFWE exhibited beneficial effects on muscle atrophy both in vitro and in vivo.